More than a feeling: Insights and information from a sentiment analysis study - Papachristopoulos, Leonidas; Tsakonas, Giannis (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2020)
Conferences have gained a significant role within the scholarly communication ecosystem as they contribute to the immediate dissemination of scientific results and, also, to the professional socialization. LIBER’s Annual Conference constitutes one of the main channels of communication for the information professionals of the European research libraries. Each year, a parallel universe arises during the conference’s activities in the social media, especially in the micro blogging sphere of Twitter, where conference attendees express their opinions about trending topics, organizational aspects and conference talks. The current study proposes that the implementation of sentiment analysis to data generated on that sphere could be a useful decision-making tool for both the organizational committee and the host organization. By applying a sentiment analysis on 5,500 tweets regarding the LIBER 47th Annual Conference in Lille, France, we highlight the positive and negative aspects of the specific event as they were mentioned by Twitter users.